Analisis Kemandirian Peserta Didik Dalam Pengembangan Lembar Kerja Siswa (LKS) Fisika Terintegrasi Materi Mitigasi Bencana Gempa Bumi Berbasis Virtual Laboratory - Ayu, Fitrah; Festiyed, Festiyed (Jurnal Penelitian Pembelajaran Fisika, 2019)
Physics is a branch of natural science that studies natural phenomena. The earthquake was one Â of the natural disasters that often hit the city of Padang. The purpose of this study was to determine the level of independence of student activity sheet integrated physics material for earthquake disaster mitigation based on a virtual laboratory. The method used in this research is qualitative method. Qualitative method is a method used to get data that contains meaning. The instrument in this study was the student questionnaire. The student questionnaire consisted of a questionnaire of independence, learning style, and earthquake disaster mitigation. The results of the independence questionnaire showed that the independence of students in the physics learning process was not optimal, the learning style of students was more dominant with the visual learning style, and the earthquake disaster mitigation of students was not optimal. So that the development of the student activity sheet based on a virtual laboratory is carried out